Nonuniform Defect Detection of Cell Phone TFT-LCD Display - Jahangir Alam S.M.; Hu Guoqing (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Uneven and Nonuniformity (Mura) of Thin Film Transistor Liquid Crystal Display (TFT-LCD) is a major problem of cell phone display. The different types of uneven and nonuniformity are decreased the performance of TFT-LCD. To economize and increase its performance, it is necessary to detect these kinds of defects. The cause of these types of noisy defects can be stimulated by the material of TFT, intensity of back light, total internal reflection, mirror form of others materials, internal light, and external light. The energy loss and gain in LCD display is another issue to make these uneven and nonuniformity. The objective of this study is to investigate and detect the defects of cell phone display considering some parameters with image analysis. The back side and the front side of the defects have been observed to find the uniqueness of that defects and its model.